SHORT CONSIDERATION REGARDING THE MEDIATION IN ROMANIA - Cîrmaciu, Diana (International Journal of Legal and Social Order, 2021)
Due to the favorable international context for the promotion and development of alternative methods of dispute resolution, mediation has also established itself in our country as an important element of the judicial reform strategy. The classic resolution of the conflict by going to court does not always appear as a covert response to the needs of the parties involved. The prolonged health crisis has repercussions in the already existing crisis of the judicial system - the high number of cases encumbering the activity of the courts, therefore, in these times any solution is welcome for the effective resolution of disputes between participants in legal relations.